2008
DOI: 10.1097/hjh.0b013e32830b61d8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic urotensin II infusion enhances macrophage foam cell formation and atherosclerosis in apolipoprotein E-knockout mice

Abstract: Our results provide the first evidence that increased plasma urotensin II level stimulates oxidized low-density lipoprotein and reactive oxygen species production and macrophage foam cell formation via increased expression of CD36, scavenger receptor class A, and acyl-CoA:cholesterol acyltransferase-1, contributing to the development of atherosclerosis in apolipoprotein E-deficient mice. Urotensin II receptor antagonism may be a promising therapeutic strategy against atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 51 publications
1
36
0
3
Order By: Relevance
“…Apoe / mice at 9 weeks of age were purchased from Sankyo Laboratory (Tokyo, Japan). The mice were maintained on an atherogenic diet containing 30% fat, 20% sucrose, 0.15% cholesterol, and 8% NaCl (Oriental Yeast, Tokyo, Japan) 13) throughout the experimental period to exacerbate atherosclerosis. After 4 weeks, the mice were randomly assigned to 5 treatment groups: saline (control), Ang , Ang GLP-1, Ang GIP, and Ang DPP-4I (MK0626; gifted by Merck Sharp & Dohme Corp., NJ, USA).…”
Section: Animal Modelmentioning
confidence: 99%
“…Apoe / mice at 9 weeks of age were purchased from Sankyo Laboratory (Tokyo, Japan). The mice were maintained on an atherogenic diet containing 30% fat, 20% sucrose, 0.15% cholesterol, and 8% NaCl (Oriental Yeast, Tokyo, Japan) 13) throughout the experimental period to exacerbate atherosclerosis. After 4 weeks, the mice were randomly assigned to 5 treatment groups: saline (control), Ang , Ang GLP-1, Ang GIP, and Ang DPP-4I (MK0626; gifted by Merck Sharp & Dohme Corp., NJ, USA).…”
Section: Animal Modelmentioning
confidence: 99%
“…Additionally, chronic UII infusion has been shown to enhance macrophage foam cell formation [12] and atherosclerosis in high-fat-fed Apoe knockout (KO) mice [13]. While UT antagonism has been investigated in diabetic nephropathy [14,15], little is known of the role of UII in the development of diabetes-associated atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…U accelerates macrophage foam cell formation by up-regulating acyl-CoA:cholesterol acyltransferase-1 38) , and has synergistic interactions with mildly oxidized LDL in inducing VSMC proliferation at the highest rate among vasoactive agents 40) . Our recent study showed that chronic infusion of U into apoE-knockout mice enhances atherosclerotic lesions 41) . These findings indicate that U contributes to the progression of atherosclerosis in the large and small cerebral arteries, leading to the major etiology of CVD followed by VaD.…”
Section: Vsmc Mø Mømentioning
confidence: 99%